TANDULIYAKA (AMARANTHUS VIRIDIS): A HIGHLY NUTRITIONAL HERB (International Journal of Ayurveda and Pharma Research, 2016)
In the past 20 years, very little progress has been achieved in reducing food insecurity, child malnutrition and hunger in Africa. Under-nutrition and micronutrients deficiencies are widespread and affect mainly women and children. To address these problems, increased consumption of African leafy vegetables is promoted as sources of both micronutrients and bio-active compounds. Widely promoted African leafy vegetables include Amaranthus sp., Species of this genus are used as pseudo-cereals in Europe and America, and are mostly planted as vegetables in Africa. Amaranthus has been rediscovered as a promising food crop mainly due to its resistance to heat, drought, diseases and pests, and the high nutritional value of both seeds and leaves. Leaves are rich in proteins and micronutrients such as iron, calcium, zinc, vitamin C and vitamin A. All parts of the plant are used as medicine to heal many diseases in African communities. Tanduliyaka (A. viridis) is grown and utilized in many areas of the world as both a wild and cultivated pot herb. The plant is rich in calcium and iron and is a good source of vitamins B and C. Due to its small seed size and use as a pot herb, A. viridis is moved, both on purpose and unwittingly, throughout the world. The seeds can survive in the digestive tract of chickens. It is good cattle fodder, and is used medicinally and for making soap, but is poisonous to pigs.